Does Money Illusion Matter? - Fehr, Ernst; Tyran, Jean-Robert (American Economic Review, 2001)
This paper shows that a small amount of individual-level money illusion may cause considerable aggregate nominal inertia after a negative nominal shock. In addition, our results indicate that negative and positive nominal shocks have asymmetric effects because of money illusion. While nominal inertia is quite substantial and long lasting after a negative shock, it is rather small after a positive shock. (JEL C92, E32, E52)